Billolivia antoanensis (Gesneriaceae), a new species from Vietnam - Nguyen, Thanh Luc; Nguyen, Tran Quoc Trung; Khieu, Duc Thinh; Luu, Hong Truong (Academia Journal of Biology, 2025)
Billolivia antoannensis is described as a new species from Central Vietnam, representing the seventeenth species in this endemic genus. The new taxon is characterized by a short and glabrous stem, thick leaves with coarsely dentate margins and glabrescent petioles, a 3–8-flowered inflorescence with short peduncle, ellipsoid calyx that is lobed to the base, glabrous or sparsely hairy bracts, and predominantly violet flowers. Detailed botanical characteristics are illustrated with field photographs. Information on the plant’s phenology, distribution, ecology, and a provisional assessment of its conservation status is also provided.